Benefícios ambientais do sistema de cultivo em aleias na eficiência do uso de nutrientes, com vistas à produção de silagem na pré-amazônia maranhense - PORTELA, Larissa Brandão (2018)
In Brazil, alley cultivation is becoming an acceptable agroforestry practice in some regions. To better understand its potential to provide environmental benefits coupled with increased productivity, research involving alley cropping systemhas expanded significantly in the last decades. With the objective of improving the productivity and sustainability indices of small farmers in the Maranhão Amazon region, an alley cropping system was used to produce corn for silageproduction. A randomized block experiment with plots of 10 x 4 m2 and four replications was used to evaluate growth and yield in the years of 2015, 2016 and 2017 and under an alley cropping system. of hybrid maize (AG1050) and QPM (BR743), usingthree species of tree legumes, Leucaena leucocephala, Gliricidia sepium and Acacia mangium. The efficiency of nitrogen use, nitrogen recovery efficiency, maize productivity, corn silage yield, carbon stock potential, decomposition and release of nutrients present in legume biomass and litter of the system, the weeding of weeds and the economic benefits, with the purpose of improving corn cultivation for silage in the Maranhão Amazon under an alley cropping system.